2017
DOI: 10.1371/journal.pone.0189877
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a smartphone app to map social networks of proximity

Abstract: Social network analysis is a prominent approach to investigate interpersonal relationships. Most studies use self-report data to quantify the connections between participants and construct social networks. In recent years smartphones have been used as an alternative to map networks by assessing the proximity between participants based on Bluetooth and GPS data. While most studies have handed out specially programmed smartphones to study participants, we developed an application for iOS and Android to collect B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…For example, radio‐frequency signals and infrared beams can be used to can detect close contact (1–5 feet) as well as directionality, which can be used to detect face‐to‐face contact between individuals (Olguín et al, ). In contrast, Bluetooth radio waves are relatively far‐ranging but provide relatively coarse spatial resolution (e.g., distinguishing whether participants are 1–2, 3–4 vs. 5–10 feet from one another) (Boonstra, Larsen, Townsend, & Christensen, ; Montanari, Nawaz, Mascolo, & Sailer, ; Osmani, Carreras, Matic, & Saar, ). However, Bluetooth is an omnidirectional signal and thus cannot be used to detect face‐to‐face contact.…”
Section: Advances In Sensing and Ubiquitous Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, radio‐frequency signals and infrared beams can be used to can detect close contact (1–5 feet) as well as directionality, which can be used to detect face‐to‐face contact between individuals (Olguín et al, ). In contrast, Bluetooth radio waves are relatively far‐ranging but provide relatively coarse spatial resolution (e.g., distinguishing whether participants are 1–2, 3–4 vs. 5–10 feet from one another) (Boonstra, Larsen, Townsend, & Christensen, ; Montanari, Nawaz, Mascolo, & Sailer, ; Osmani, Carreras, Matic, & Saar, ). However, Bluetooth is an omnidirectional signal and thus cannot be used to detect face‐to‐face contact.…”
Section: Advances In Sensing and Ubiquitous Computingmentioning
confidence: 99%
“…However, Bluetooth is an omnidirectional signal and thus cannot be used to detect face‐to‐face contact. While it is technically possible to obtain Bluetooth scans every 5–20 s, on most cell phones it is only feasible to log scans once every five minutes or so due to battery constraints (Boonstra et al, ).…”
Section: Advances In Sensing and Ubiquitous Computingmentioning
confidence: 99%
“…For example, we used push notifications and the Significant-Change Location Service to successfully increase data completeness on iOS devices compared to previous studies showing a significant disparity between Android and iOS data acquisition rates [20,21]. With the current version of the app, we no longer have a significant difference between Android and iOS data completeness.…”
Section: Discussionmentioning
confidence: 99%
“…We developed Socialise as a native application in Java for Android and Objective-C for iOS in order to collect passive data (Bluetooth and GPS) and Ecological Momentary Assessment (EMA). Building on the results of a previous validation and feasibility study [20,21], we have implemented several changes to improve scanning rates on iOS and here we tested Socialise version v0.2.…”
Section: Methodsmentioning
confidence: 99%
“…These data have been widely used to investigate the structure of social networks, the patterns of social interactions and social theories, such as the strength of weak ties [7], homophily patterns (the tendency of individuals to have social links with similar individuals, with respect to gender, nationality, social class, etc.[10]) [11][12][13][14][15][16], mechanisms of link formation and persistence [11,12,17], social strategies linked to limited attention capacity [8], etc.In most cases, such studies are based on data describing one specific layer of the multilayer network characterizing social interactions, and consider this layer as a proxy of "the" social network of the population under study. Several research groups have, however, managed in recent years to access simultaneously more than one layer of interactions in various population groups, showing in each case that these layers are correlated but not equivalent [4,[18][19][20][21][22][23][24]. For instance, a comparison between face-to-face contacts measured by sensors and friendship relations obtained through surveys has shown that the distribution of contact durations are broad both for pairs of friends and pairs of non-friends, even if the longest contacts occur between friends [20].…”
mentioning
confidence: 99%